Crossing the Borders of the Literary Markets: The Main Implications for the Early Transmission of Knut Hamsun's Works in Germany and the Key Figures Involved in it - Wenusch, Monica (Nordlit, 2020)
Without any doubt, Knut Hamsun has earned the status as one of the most prominent Norwegian representatives of world literature as his works were and still are widely translated and distributed internationally. Crucial to the author’s international recognition was his own border-crossing away from Norway, not least to one of the literary centres of the time, Paris, where Hamsun stayed two times between April 1893 and June 1895. Here, he got acquainted with his future German publisher, Albert Langen. Allegedly, Albert Langen Verlag was even founded because of Hamsun. Nevertheless, Hamsun’s first book publication in German translation appeared at S. Fischer Verlag. Both publishing houses were explicitly renowned for their dissemination of Scandinavian literature in translation. This article focuses on the main implications of the early transmission, dissemination and circulation of Hamsun’s works in Germany and the key figures involved in it.
Keywords: Hamsun; early transmission; German book market; intermediaries; translators